اللاارتياح في وضعية الوقوف لدى عمال البناء دراسة ميدانية على عينة من عمال البناء لبلدية الرباح - غربي, البشير; محجر, ياسين (جامعة الوادي - University of Eloued, 2022)
ملخص: هدفت هذه الدراسة الى الكشف عن مواطن الاكثر لا ارتياحا في الجسم من وجهة نظر عمال البناء والاضرار التي يمكن ان تنجر عن وضعيات الوقوف غير الصحيحة، حيث تمت الدراسة على عينة قوامها 30 عامل ، تم استخدام المنهج الوصفي الاستكشافي ذلك لملائمته لطبيعة الدراسة، وتم استخدام طريقة بيشوب وكرولات (1970) لمعرفة مدى اللاارتياح في وضعية الوقوف، لتتم تحليل النتائج بوسطة مقاييس النزعة المركزية، و توصلت الدراسة الى أن عمال البناء يشعرون بعدم ارتياح في موطن الجسم خلال وضعية الوقوف وهي (منطقة أسفل الظهر، الكتفين، الركبتين، الفخذين، اليدين، الرجلين) الكلمات المفتاحية: عدم الارتياح؛ وضعية الوقوف؛ عمال البناء؛ وضعيات العمل. Abstract: This study aimed to reveal the most uncomfortable places in the body from of the construction workers , and the damages that can result from incorrect sitting postures. Where the study was conducted on a sample of 30 Building. The exploratory descriptive method was used suit the nature of the study, The method of Bishop and Crollette (1970) was used to determine the discomfort in the standing position. The results are analyzed using measures of central tendency. The study found that university employees feel uncomfortable in the body’s position during the sitting posture (lower back, shoulders, knees, Thighs, hands, the two men (
Construction workers uncomfortable position A field study on a sample of construction workers for the city of Al-Robbah
مقال
Keywords: عدم الارتياح، وضعية الوقوف، عمال البناء، وضعيات العمل.; discomfort, standing position, construction workers, working postures.